Anatomic and functional discordance among patients with non-obstructive coronary disease. (3rd October 2022) - Rymer, J; Takagi, H; Koweek, L; Ng, N; Douglas, P; Fairbairn, T; Berman, D; De Bruyne, B; Bax, J J; Nieman, K; Rogers, C; Noorgaard, B L; et al.
Abstract: Background: Non-obstructive coronary artery disease (CAD) is associated with increased adverse cardiovascular (CV) events. However, it is unclear if functional stenosis, as assessed by FFRCT <0.80, further stratifies risk among patients with non-obstructive CAD and which factors contribute to this anatomic-functional discordance (stenosis <50% and FFRCT <0.80). Purpose: We hypothesized that patients with anatomically non-obstructive CAD by CTA and an abnormal FFRCT value of ≤0.80 have a phenomenon termed anatomic-functional discordance, and this discordance would be associated with increased adverse outcomes. Methods: Patients in the ADVANCE (Assessing Diagnostic Value of Non-invasive FFRCT in Coronary Care) Registry who had exclusively non-obstructive CAD (anatomic stenosis <50%) were stratified by FFRCT >0.80 in all coronary vessels (concordant) vs. FFRCT <0.80 in at least one vessel (discordant). Baseline patient demographics, coronary computed tomography angiography findings, downstream testing and clinical outcomes were compared between groups. The primary composite endpoint included revascularization, CV hospitalization, heart failure, arrhythmia, non-fatal myocardial infarction, unplanned hospitalization for an acute coronary syndrome leading to urgent revascularization, and all-cause death. Results: Among 1, 261 patients with non-obstructive CAD, 543 (43.1%) had functional stenosis with FFRCT <0.80. Patients in the discordant group were older, more likely to have hypertension, hyperlipidemia, and had significantly higher indexed left ventricular (LV) mass and significantly lower coronary volume-to-mass ratios when compared with patients in the concordant group. Downstream non-invasive testing was more common among patients with discordance (35.9% vs 20.2%, p<0.0001) and more frequently resulted in a positive downstream test (10.3% vs. 3.3%, p<0.0001). Invasive angiography was also more common among patients with discordance (25.2% vs. 11.6%, p<0.0001). Anatomic-functional discordance was associated with higher rates of CV hospitalization and percutaneous coronary intervention (both p<0.0001), but no significant difference in all-cause death. After adjustment, anatomic-functional discordance was associated with a significantly higher risk of the composite endpoint (adjusted HR 2.79, 95% CI 1.67–4.65), Figure 1. As shown in Figure 2, the more vessels with anatomic-functional discordance, the higher the rate of adverse cardiac events. Conclusion: Anatomic-functional discordance was present in nearly half of patients with exclusively non-obstructive CAD. The lower coronary volume: LV mass ratio may reflect abnormal coronary physiology at lower thresholds of anatomical stenosis among those with discordance. Compared to patients with concordance, patients with discordance had worse clinical outcomes suggesting that anatomic-functional discordance may stratify risk for adverse CV events among patients with non-obstructive CAD. Funding Acknowledgement: Type of funding sources: Other. Main funding source(s): The analysis was an investigator-initiated analysis sponsored by Heart Flow.